Unlocking further understanding of the atomization mechanism of a pressurized metered dose inhaler. Issue 11 (29th September 2022) - Myatt, B. J.; Versteeg, H. K.; Hargrave, G. K.; Long, E. J.; Gavtash, B.; Lewis, D. A.; Church, T.; Brambilla, G.
Abstract: Pressurized metered dose inhalers (pMDI) are one of the most common devices to deliver therapeutic treatment to patients with asthma or COPD. The atomization mechanism responsible for droplet production is poorly understood because of the short length and timescales involved, making experimental investigations to characterize fluid flow structures and spray formation processes difficult. This article reports the findings of new high-speed and high-resolution imaging and temperature measurements seeking to improve the fundamental understanding of the atomization mechanism of the pMDI. An annular flow regime of gaseous core in liquid annulus was observed in the orifice. Shock diamonds within the flow, viewed via Schlieren imaging, confirmed experimentally for the first time the choked nature of the orifice exit flow. Propellant formulation flow in the orifice was found to be superheated to a degree that significant flashing and evaporation at the orifice exit is likely to take place. This information points to a hybrid mechanism of predominantly aerodynamic atomization with significant liquid flashing upon exit from the orifice producing a near instantaneous formation of respirable droplets. Large irrespirable droplets are produced by two mechanisms; breakup of liquid slugs ejected from the orifice, due to unsteady transient fluid structures in the actuator sump and stripping of ligaments from a liquid pool around the orifice exit, which subsequently break up into large droplets in the periphery of the plume. This new understanding will aid development of next generation, high efficiency pMDIs, particularly those employing low global warming potential propellants such as HFA152a or HFO1234ze(E). Copyright © 2022 American Association for Aerosol Research